2014
DOI: 10.1186/1476-069x-13-85
|View full text |Cite
|
Sign up to set email alerts
|

Spatiotemporal association between birth outcomes and coke production and steel making facilities in Alabama, USA: a cross-sectional study

Abstract: BackgroundPrevious research has shown exposure to air pollution increases the risk of adverse birth outcomes, although the effects of residential proximity to significant industrial point sources are less defined. The objective of the current study was to determine whether yearly reported releases from major industrial point sources are associated with adverse birth outcomes.MethodsMaternal residence from geocoded Alabama birth records between 1991 and 2010 were used to calculate distances from coke and steel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
12
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 28 publications
3
12
0
1
Order By: Relevance
“…A similar association between preterm and coke production and steel making facilities has been observed by a recent study in the US (Porter et al, 2014). It may be possible that preterm births and miscarriages share common causal factors implied in the termination of pregnancy (Saraswat et al, 2010).…”
Section: Discussionsupporting
confidence: 52%
“…A similar association between preterm and coke production and steel making facilities has been observed by a recent study in the US (Porter et al, 2014). It may be possible that preterm births and miscarriages share common causal factors implied in the termination of pregnancy (Saraswat et al, 2010).…”
Section: Discussionsupporting
confidence: 52%
“…The county-level predictive measures of LBW offers new insights into spatiotemporal patterns relative to key contributory factors. The findings in this study provide further evidence and are consistent with previous studies that have identified socioeconomic [ 29 , 30 , 31 , 32 , 33 , 34 , 35 ], behavioral [ 36 , 37 , 38 ], and environmental factors [ 39 , 40 , 41 , 42 , 43 ]. By means of our external exposome approach, we observed that LBW rate was more strongly associated with 17 variables.…”
Section: Discussionsupporting
confidence: 92%
“…Specific exposures include fine particulate air particles, carbon monoxide, and ozone. Other studies examine the impact of residing near chemical plants, refineries, or other industries (48)(49)(50)(51)(52)(53)(54)(55)(56)(57)(58)(59). There are also studies that suggest that racial/ethnic minorities are at greater likelihood of residing in communities with higher pollution rates, based on monitoring data from the Environmental Protection Agency (57).…”
Section: Physical Environmentmentioning
confidence: 99%